FE-SEM Evaluation of Dental Specimens Prepared by Different Methods for In Vitro Contamination - Vitor Cesar Nakamura; Simony Hidee Hamoy Kataoka; Giulio Gavini; Patrícia Helena Ferrari; Silvana Cai (Hindawi Limited, 2012)
Objective. To evaluate through FE-SEM the cleanliness and dentinal alterations promoted by different methods of dental sample preparation. Methods. Twenty-five human single-rooted teeth were used. The teeth were cleaned and autoclaved in wet medium and randomly divided into 5 groups (𝑛=5), according to the preparation methods employed-control group: no solutions applied; group 1: cement removal and irrigation with 5.25% NaOCl+17 % EDTA for 4 minutes each; group 2: 17%  EDTA+2.5% NaOCl (4 minutes ultrasonic bath); group 3: cement removal and 17%  EDTA+5.25%  NaOCl+phosphate buffer solution + distilled water (10 minutes ultrasonic); group 4: 17%  EDTA+5.25% NaOCl (3 minutes ultrasonic bath). Specimens were analyzed by field emission scanning electron microscope (FE-SEM), at 1500x magnification. Data were submitted to qualitative analysis according to a scoring system and submitted to Kruskal-Wallis test. Results. In ascending order, as to bind parameters, (i) cleanliness: control, group 2, group 3, group 5, and group 4, (ii) dentinal alterations: group 1, group 5, group 2, group 3, and group 4. Conclusion. The proposed protocol was suitable for subsequent microbiological contamination, because it showed less dentinal morphological alterations with increased removal of organic waste.